Controlling light absorption and transmission in graphene-embedded structure with Fano resonance and FP resonance. (December 2018) - Chen, Yuwei; Bian, Li-an; Liu, Peiguo; Li, Gaosheng; Xie, Yuchen
Abstract: Near-unity absorption and transmission are achieved in the subwavelength grating and graphene-coated defective photonic crystal compound. Two absorption modes appear due to the Fano resonance in the grating, and a single transmission mode as defect mode is exhibited thanks to the Fabry-Perot (FP) resonance in photonic crystal. At approaching critical coupling, the absorption reaches near-unity level. By changing the chemical potential of graphene, the geometries of grating and the defect cavity of photonic crystal along with the angle of incident light, absorption modes and the transmission mode can be controlled flexibly. The multifunction structure with absorbing and filtering capabilities simultaneously should be applicable to guarantee the pass of target signal and absorb the interference signals. Highlights: Near-unity absorption and transmission is achieved simultaneously in graphene-embedded compound structure. At approaching critical coupling, two near-unity absorption modes appear due to Fano resonances in grating. One near-unity transmission mode is excited in defective photonic crystal. The absorption modes and transmission mode can be tuned independently.